Pre-exposure Prophylaxis With Tenofovir Disoproxil Fumarate/Emtricitabine and Kidney Tubular Dysfunction in HIV-Uninfected Individuals. (1st June 2018) - Jotwani, Vasantha; Scherzer, Rebecca; Glidden, David V.; Mehrotra, Megha; Defechereux, Patricia; Liu, Albert; Gandhi, Monica; Bennett, Michael; Coca, Steven G.; Parikh, Chirag R.; Grant, Robert M.; Shlipak, Michael G.
Abstract : Background: Pre-exposure prophylaxis (PrEP) with tenofovir disoproxil fumarate (TDF) and emtricitabine (FTC) is becoming increasingly adopted for HIV prevention. Tenofovir can cause proximal tubular damage and chronic kidney disease in HIV-infected persons, but little is known regarding its nephrotoxic potential among HIV-uninfected persons. In this study, we evaluated the effects of PrEP on urine levels of the following: α1-microglobulin (α1m), a marker of impaired tubular reabsorption; albuminuria, a measure of glomerular injury; and total proteinuria. Setting: The Iniciativa Profilaxis Pre-Exposicion (iPrEx) study randomized HIV-seronegative men and transgender women who have sex with men to oral TDF/FTC or placebo. The iPrEx open-label extension (iPrEx-OLE) study enrolled former PrEP trial participants to receive open-label TDF/FTC. Methods: A cross-sectional analysis compared urine biomarker levels by study arm in iPrEx (N = 100 treatment arm, N = 100 placebo arm). Then, urine biomarker levels were compared before and after PrEP initiation in 109 participants of iPrEx-OLE. Results: In iPrEx, there were no significant differences in urine α1m, albuminuria, or proteinuria by treatment arm. In iPrEx-OLE, after 24 weeks on PrEP, urine α1m and proteinuria increased by 21% [95% confidence interval (CI): 10 to 33] and 18% (95% CI: 8 to 28), respectively. The prevalence of detectable α1m increased from 44% to 65% ( P < 0.001) and estimated glomerular filtration rate declined by 4 mL/min/1.73 m 2 ( P < 0.001). There was no significant change in albuminuria (6%; 95% CI: −7% to 20%). Conclusion: PrEP with TDF/FTC was associated with a statistically significant rise in urine α1m and proteinuria after 6 months, suggesting that PrEP may result in subclinical tubule dysfunction. Abstract : Supplemental Digital Content is Available in the Text.